(untitled) (Faculty of Education Scientific Journal, 2024)
The research aims to reveal the effect of an experimental program based on the use of folk games in developing social interactions among a sample of kindergartens in the city of Misrata. The research sample consisted of a sample of (20) male and female children, aged between (4-5) years, males. And females, they were selected from Lamasat Kindergarten in the city of Misrata. The members of the research sample were classified into one as experimental and the other as control, each consisting of (10) children. The researcher used the experimental approach with an experimental design for the experimental and control groups. To achieve the objectives of the research, the scale of social interactions was used. A counseling program was built based on popular games, consisting of 12 sessions. The validity and stability of the research tools were verified and then applied to the sample. The results resulted in no statistically significant differences in the pre-scale between the experimental group and the control group. The results also show the presence of There are statistically significant differences in the post-measurement between the experimental group and the control group in favor of the experimental group. There are also statistically significant differences between the average responses of the children in the pre-measurement and the post-measurement of the experimental group, and there are also no statistically significant differences between the average responses of the children in the pre-measurement and the post-measurement. Post-test for the control group.